The Role of Coastal Women in Seaweed Farming to Support Value Chains Development in Saronggi Subdistrict, Sumenep: Peran Perempuan Pesisir dalam Budidaya Rumput Laut Guna Pengembangan Rantai Nilai di Kecamatan Saronggi, Sumenep - Aninda Intan Narulita; Dwi Ratna Hidayati; Mokh Rum; Baiq Yulfia Elsadewi Yanuartati (Jurnal Ilmiah Sosio Agribis, 2026)
Seaweed is a key commodity in Saronggi District, Sumenep Regency, East Java Province, contributing significantly to the regional economy. Cultivation is the first and most critical stage in the seaweed value chain, and it involves coastal women who play important roles from pre-production to post-harvest. This study aims to identify the specific roles and contributions of women in seaweed farming and to compare them with men's roles across production stages, as well as to examine how gender dynamics affect the sustainability and performance of the value chain. A qualitative and quantitative descriptive approach was used, with data collected from 30 female respondents through interviews and direct observation. The results show that women dominate pre-production activities, particularly seed cutting (93%) and seed tying (97%). Their involvement is lower during planting. Post-harvest activities are typically carried out jointly by men and women. Meanwhile, processing activities undertaken by women exist but are mainly for subsistence or non-commercial purposes and do not directly contribute to commercial outcomes. These findings indicate that while women's roles are limited, they remain critical to supporting production and the future development of the seaweed value chain in the region.